Development of a multi-access key to the ferns of Thailand - Lindsay, Stuart; Middleton, David J. (Thai Forest Bulletin (Botany), 2014)
This paper explains why the fern account in the Flora of Thailand needs to be updated and provides details of a project to develop a web-accessible multi-access key that incorporates these updates.